Typification of Láng’s names in Polycnemum (Amaranthaceae s.l.) - Iamonico, Duilio; Somlyay, Lajos (Phytotaxa, 2014)
As part of the treatment of Polycnemum by D. Iamonico for a new edition of the Flora of Italy (e.g., Iamonico 2011, 2012, 2013), and the ongoing taxonomic revision of the genus in Europe (Iamonico et al., in prep.), we hereby typify the names in Polycnemum Linnaeus (1753: 35) introduced by the Hungarian pharmacist and botanist, A.F. Láng (1795–1863). Láng’s contribution to European Polycnemum taxonomy was substantial, because of the currently accepted four species (Ball 1993), two [P. heuffelii Láng (1828: 219), P. verrucosum Láng (1824: 179)] were described by him. The greatest part of his huge herbarium (ca 60.000 specimens) was moved to Austria (Gombocz 1936), but many of his specimens are scattered in different herbaria worldwide.